Boosting Tissue Vascularization: Nanofat as a Potential Source of Functional Microvessel Segments - Weinzierl, Andrea; Harder, Yves; Schmauss, Daniel; Menger, Michael D.; Laschke, Matthias W. (Frontiers in Bioengineering and Biotechnology, 2022)
Nanofat is increasingly applied in plastic surgery for the improvement of scar quality and skin rejuvenation. However, little is known about the underlying regenerative mechanisms. Therefore, we herein investigated for the first time the in vivo vascularization capacity of nanofat grafts in a murine dorsal skinfold chamber model. Nanofat generated from subcutaneous, inguinal adipose tissue of green fluorescent protein (GFP)+ C57BL/6 male and female donor mice was injected subcutaneously into dorsal skinfold chambers of gender-matched GFP- wild-type mice. The vascularization and tissue composition of the grafted nanofat were analyzed by means of intravital fluorescence microscopy, histology and immunohistochemistry over an observation period of 14 days. The freshly generated nanofat consisted of small fragments of perilipin+ adipocytes surrounded by Sirius red+ collagen fibers and still contained intact CD31+/GFP+ vessel segments. After transplantation into the dorsal skinfold chamber, these vessel segments survived and developed interconnections to the surrounding CD31+/GFP- host microvasculature. Accordingly, the grafted nanofat rapidly vascularized and formed new microvascular networks with a high functional microvessel density on day 14 without marked differences between male and female mice. These findings indicate that nanofat effectively boosts tissue vascularization and, thus, may represent a versatile resource for many applications in tissue engineering and regenerative medicine.